The role of fiqh education in shaping student character: A study at man wonogiri - Lusiana Rachmawati; Amir Mukminin; Mohammad Farhan Zeb Khan (Yayasan Azhar Amanaa Yogyakarta, 2025)
Fiqh learning has an important role in shaping the character of students, but in reality there are still many students who have not shown character in accordance with the Islamic values learned in fiqh. This condition can be seen from the presence of students who are not disciplined in worship, lack of respect for teachers, and behavior that does not reflect noble character. This study aims to analyze the role of fiqh learning in building the character of grade XI students at Madrasah Aliyah Negeri Wonogiri and identify the supporting and inhibiting factors. The research method uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results showed that fiqh learning plays a role in building religious character, discipline, responsibility, and social care through the integration of character values in learning materials, teacher exemplary, and habituation of worship practices. The impact of fiqh learning can be seen from the increasing awareness of students in carrying out worship, respect for teachers, and concern for others. This research contributes to the development of effective fiqh learning strategies for character building.